Student Participation in European Governance - Klemencic, Manja (International Higher Education, 2012)
Although student participation in HE governance continues to be a value in Europe, the terms of participation are rapidly changing. The reasons lie broadly in the modernisation agenda for European universities: new public management approach in institutional governance and rising tuition fees. As a result, institutional preference for student participation is changing from decision-making function in governing towards an advisory function in quality assurance and new styles of student engagement in institutional efforts to enhance student experience and in the student centered learning. In other words, while the formal student participation in governing appears to be weakening, the informal student participation is strengthening.